Effect of methyl jasmonate on the quality of harvested broccoli after simulated transport. (30th July 2020) - Xu, Dongying; Zuo, Jinhua; Li, Peiyun; Yan, Zhicheng; Gao, Lipu; Wang, Qing; Jiang, Aili
Highlights: Vibration injury promoted a decline in the postharvest quality of broccoli florets. MeJA ameliorated the reduction in broccoli quality caused by simulated transport vibration. The inhibition of broccoli senescence by MeJA was associated with the induction of antioxidant system. MeJA delayed floret yellowing by regulating chlorophyll metabolism. Abstract: The effect of simulated transport vibration on the quality of broccoli and the ability of methyl jasmonate (MeJA) to ameliorate vibration damage in broccoli were investigated. Results indicated that transport injury, simulated by vibrational stress, promoted the deterioration in broccoli quality during subsequent storage. Treatment of broccoli with methyl jasmonate (MeJA), however, effectively ameliorated the impact of vibrational injury, maintained the appearance quality and delayed the yellowing and senescence of florets after simulated transportation stress. The effect of the MeJA may be related to of its ability to suppress the accumulation of reactive oxygen species, enhance vitamin C content, and induce antioxidant gene expression and enzyme activity, as well as suppress chlorophyll-degrading enzyme activity and gene expression. Overall, the MeJA treatment inhibited the adverse physiological changes that occur in broccoli as a result of vibrational and mechanical injury. Thus, MeJA has the potential to be used to decrease stress-induced reductions in the postharvest quality of horticultural crops that occur during transport and storage, thus, prolonging their shelf life.